Особенности сельскохозяйственной информации - Зинкявичене, Юлия (Knygotyra, 1987)
We pay great attention to the development of agriculture which is the essential part of the national economy and plays the key-role in the realization of the food programme.The perfection of the system of agricultural information is the great importance in the fulfilment of the task of the intensification of agriculture. In this article he author analizes the specific features of the system of agricultural information and presents the negative and positive sides of the information services in this field with regard to the existing situation and the organization of this system in our country.